Evaluation of community pharmacists’ readiness to implement the Falsified Medicines Directive (Directive 2011/62/EC): an English cross-sectional survey with geospatial analysis - Ravina Barrett (BMJ Open)
Objectives To evaluate the readiness to implement the Falsified Medicines Directive (FMD) by community pharmacies in England. Eight secondary objectives were assessed.Setting Community/retail pharmacies.Participants We invited pharmacists from 501 pharmacies to complete a survey. Non-contractors, non-pharmacists or pharmacists practising abroad were excluded. We randomly selected addresses, ensuring that they were nationally representative.Interventions We mailed the survey in October 2018 with a single follow-up in January 2019. Respondents were invited to provide self-reported answers. A prepaid self-addressed envelope was provided. We received favourable ethical approval.Results 102 responses (20.44% response rate) were received. Readiness to implement was poor: 4 (3.9%) said very much, while 40 (39.2%) said not at all and 29 (28.4%) said not really. Increased workload and reduced profitability were anticipated, accompanied with improved patient safety. Prevalence of ‘substandard and falsified (SF) medical products’ was estimated at 1%–5%, with erectile dysfunction at greatest risk of falsification. Different packaging would raise suspicions. Five (4.9%) had identified SFs (p<0.001 one-sample binomial test). Of these, three (2.9%) informed the medicines agency. None had been involved in any public health campaigns. Confidence and self-efficacy was low. Strategies to reduce SFs reaching the public are described. Pharmacist’s role in combating SFs was elucidated. SFs were identified in deprived areas 4 (9%) more often than in affluent areas 1 (2%).Conclusions Many pharmacies are not ready to implement FMD, potentially not capturing anticipated benefits of the directive, with greatest risk of harm in deprived area. We further validated a confidence scale. Limited public health campaigns may result in a lack of awareness among pharmacy professionals and patients. Limited awareness of technologies to identify falsified medicines exist, though further training is welcome. A worrying trend of under-reporting maybe prevalent. A larger sample study using this survey would be valuable.